Monitoring Arus dan Temperature Discharge Kompresor Berbasis IoT (Internet of Things) untuk Kebutuhan Preventive Maintenance di PT. Mekar Armada Jaya - Damar Romansdani; Pudin, Apip; Budi Mursanto, Wahyu (SURYA TEKNIKA, 2024)
Preventive maintenance monitoring of current and compressor discharge temperature is essential to prevent damage to the machine and to assess the performance of each component. It helps to determine whether they are working properly or not. It also improves safety and reduces the risk of production downtime. The study focuses on developing and testing an IoT-based preventive maintenance monitoring system at PT. Mekar Armada Jaya. The system uses a thermocouple type K sensor for temperature discharge monitoring, a PZEM-004T module for current parameter readings, and a relay to interrupt the power flow in case of overheating. In addition, an ESP-8266 device processes the data from the sensors and displays it via the Blynk interface. The average measurement difference percentages for the current test on the resistor bank were as follows Phase R = 0.10%, Phase S = 0.40%, and Phase T = 0.67%. When testing the thermocouple type K sensors for hot water temperatures, the average percentages of reading measurement difference is 0.2% with an average difference of 0.08°C. The overheat relay test performed well, interrupting system flow when the reading reached 105°C.